2014
DOI: 10.1126/scitranslmed.3008604
|View full text |Cite
|
Sign up to set email alerts
|

Biobanks and Electronic Medical Records: Enabling Cost-Effective Research

Abstract: The use of electronic medical record data linked to biological specimens in health care settings is expected to enable cost-effective and rapid genomic analyses. Here, we present a model that highlights potential advantages for genomic discovery and describe the operational infrastructure that facilitated multiple simultaneous discovery efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 35 publications
0
111
0
Order By: Relevance
“…The coding definition excluded two ICD-9-CM groups: 'nephritis, nephrotic syndrome and nephrosis' (580-589) and 'other diseases of urinary system' (590-599). However, a substantial proportion (11.2%) of patients in this study had undergone a kidney transplant [45,56]. Because of the strong correlation between renal osteodystrophy diagnoses and kidney transplant in this dataset (r ϕ = 0.82, p > 10 -20 ), we retested the association between SLC15A2 rs1143672 and renal osteodystrophy after adjustment for kidney transplant status and found that the association was not significant (p = 0.22).…”
Section: Novel Associations Among European-americansmentioning
confidence: 99%
See 1 more Smart Citation
“…The coding definition excluded two ICD-9-CM groups: 'nephritis, nephrotic syndrome and nephrosis' (580-589) and 'other diseases of urinary system' (590-599). However, a substantial proportion (11.2%) of patients in this study had undergone a kidney transplant [45,56]. Because of the strong correlation between renal osteodystrophy diagnoses and kidney transplant in this dataset (r ϕ = 0.82, p > 10 -20 ), we retested the association between SLC15A2 rs1143672 and renal osteodystrophy after adjustment for kidney transplant status and found that the association was not significant (p = 0.22).…”
Section: Novel Associations Among European-americansmentioning
confidence: 99%
“…The clinical characteristics of the study population are shown in Table 1. A total of 7266 DNA samples were genotyped using the Illumina ® ADME Core Panel, which has been used for previous pharmacogenetic studies in BioVU (Supplementary Table 1) [45]. After quality control (see 'Methods'), the majority of the samples were European-American (n = 6067) and the remainder African-American (n = 762).…”
Section: Study Populationmentioning
confidence: 99%
“…Using automated phenotyping algorithms, investigators have identified cases and controls for diseases of interest to replicate known phenotype-genotype associations and make novel discoveries, [12][13][14][15][16][17] potentially with decreased cost 18 and faster execution than traditional trials.…”
Section: Background and Significancementioning
confidence: 99%
“…The combination of a highvolume clinical center and established EMRs allows investigators to identify large cohorts for most clinical phenotypes. Bowton et al 32 recently showed that the median cohort size for 28 validated phenotypes in Vanderbilt's Synthetic Derivative was 1,123 (interquartile range [IQR]: 492-4,158) subjects, compared with 623 (IQR: 273-2,095) subjects in similar cohort studies funded by the National Institutes of Health. Moreover, the median time to construct the EMR-based cohorts was 3 months, compared with 3 years for NIHfunded cohorts.…”
Section: Emr-based Cohorts Versus Traditional Prospective Cohortsmentioning
confidence: 99%